Simple finite-control-set model predictive control method for reducing common mode voltage in a three phase two-level voltage source inverter - Fatima Abdelaziz; Zin-Eddine Azzouz; Abdelhafid Omari (Institute of Advanced Engineering and Science, 2022)
The common mode voltage (CMV) causes many issues and negatively affects the performance of the power system in a hybrid electric vehicle HEV. Therefore, this paper suggests a simple method for mitigating the common mode voltage CMV in a two level three phase voltage source inverter VSI with RL load. Hence, the technique chosen for this purpose is based on model predictive control. Otherwise, when compared to the standard method, this simple method can successfully mitigate CMV while also improving harmonic performance by lowering the total harmonic distortion THD. The purpose of this paper is reducing THD and CMV simultaneously utilizing only non-zero vectors. According to simulation results obtained by MATLAB-Simulink, this simple solution reduced CMV to ±???????????? 6 and THD from 3.49% to 3.39 % (10 % improvement) compared with the standard method, which mitigates CMV using the cost function.